Efficacy of Combination Therapy with Telmisartan Plus Amlodipine in Patients with Poorly Controlled Hypertension. Issue 5 (2010) - Bekki, Hisatoshi; Yamamoto, Kiichiro; Sone, Masayoshi; Homma, Tomoki; Nakata, Masashi; Nohara, Masatoshi; Fukami, Kei; Okuda, Seiya; Yamagish, Sho-ichi
Abstract : There is accumulating evidence that blood pressure (BP) control significantly reduces the risk of future cardiovascular events in patients with essential hypertension. However, strict BP control is often difficult to maintain, and half of hypertensive patients fail to attain BP goals on single-drug therapy. Therefore, current guidelines recommend combinations of drugs that have complimentary mode of actions for treatment of patients with moderate hypertension. In this study, we examined in hypertensive patients uncontrolled by the combination treatment with 5 mg amlodipine plus 80 mg valsartan or 8 mg candesartan whether additional BP lowering could be achieved by switching to 5 mg amlodipine plus 40 mg telmisartan. Forty-seven patients with essential hypertension who failed to achieve a target BP level by the treatment of 5 mg amlodipine plus 80 mg valsartan or 8 mg candesartan for at least 2 months were enrolled. Replacement of valsartan or candesartan by telmisartan showed a significant reduction in both mean clinic systolic and diastolic BP at 4, 8 and 12 weeks; BP level decreased from 143.7/82.3 mmHg at baseline to 135.4/77.5 mmHg at 12 weeks. Furthermore, in 8 patients of valsartan group, switching to telmisartan significantly reduced central BP by 11.8 mmHg. Our present study suggests that combination therapy with telmisartan plus amlodipine may be more beneficial than valsartan or candesartan plus amolodipine treatment for controlling brachial and central BP, which could lead to more favorable cardiovascular outcomes with this drug combinations.